1995
DOI: 10.1097/00000658-199505000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dopamine and Dobutamine on Regional Blood Flow Distribution in the Neonatal Piglet

Abstract: Dopamine may prove a valuable adjunct when a premature infant is at risk for conditions that reduce alimentary tract blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 14 publications
4
37
0
Order By: Relevance
“…The effects of dobutamine on hepatosplanchnic hemodynamics are controversial and dependent on the concomitant changes in cardiac output. In most studies, splanchnic blood flow has increased because of dobutamine therapy (13, 31Y35), whereas some studies have reported unchanged (36) or decreased (19,37,38) splanchnic blood flow during dobutamine treatment without detailed assessment of pressure-flow relationships. Because we did not assess the pressure-flow relationship in detail either, the effects of dobutamine on the vascular tone must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of dobutamine on hepatosplanchnic hemodynamics are controversial and dependent on the concomitant changes in cardiac output. In most studies, splanchnic blood flow has increased because of dobutamine therapy (13, 31Y35), whereas some studies have reported unchanged (36) or decreased (19,37,38) splanchnic blood flow during dobutamine treatment without detailed assessment of pressure-flow relationships. Because we did not assess the pressure-flow relationship in detail either, the effects of dobutamine on the vascular tone must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Both in preterm newborns and animal models low doses of dopamine induce superior mesenteric artery vasodilation and reduce pulsatility index without affecting systemic BP, similarly to what observed in term neonates and adults [28,60,64]. However, further observations suggest that dopamine enhances blood flow in the renal district but not in the mesenteric one in VLBW infants [54], probably because of functionally immature dopaminergic response of the mesenteric vasculature [54].…”
Section: Indications To Dopamine Treatment In Vlbw Infantsmentioning
confidence: 61%
“…Ultrasound measurements demonstrated increased blood flow in the superior mesenteric artery following dopamine administration both in term and preterm neonates [60,64]. Although certain observations do not agree with the occurrence of mesenteric vasodilation in the preterm population [28,65], the improvement of splanchnic perfusion in VLBW infants would be of considerable clinical importance, considering the close relation between poor local perfusion and risk of necrotizing enterocolitis.…”
Section: Other Systemsmentioning
confidence: 98%
“…Similarly, some of the studies showed an increase in heart rate in a dose-dependent manner [5], [9], [11][13], [16], [18], [23], [26], [28]. An increase in stroke volume was mainly observed in studies using prolonged infusion (from 2 to 6 h) at doses higher than 10 µg/kg/min [6], [8], [9], [17].…”
Section: Resultsmentioning
confidence: 84%
“…Some found no changes in arterial blood pressure [7][9], [17], [20], [24], [28], but in a few studies the arterial blood pressure increased at the highest dose studied [6], [11], [19], [26], [27]. Similarly, some of the studies showed an increase in heart rate in a dose-dependent manner [5], [9], [11][13], [16], [18], [23], [26], [28].…”
Section: Resultsmentioning
confidence: 97%